STALOWA WOLA – THE CITY OF BIG INVESTMENTS. HISTORY, THE PRESENT, THE FUTURE - Anna Sikora; Marek Kowal (Journal of Civil Engineering, Environment and Architecture, 2021)
After regaining independence in 1918, Poland faced the task of rebuilding its infrastructure. One of the main achievements, apart from the port of Gdynia, was Stalowa Wola – a city built on a “raw root” with a closed, avant-garde composition, which was largely realized. The appearance of the city was influenced by the doctrines: modernist (including socialist modernism) and socialist realist. The article presents a design procedure model that can be used in the case of designing areas with the morphogenesis of a modernist city. The proposed method uses the theoretical considerations of Aldo Rossi and Jan Gehl and the elements of User Experience Design (UX).